Pemberian Kalsium Laktat dan Berenang Meningkatkan Osteoblast pada Epiphysis Tulang Radius Mencit Perimenopause (ORALLY LACTATE CALCIUM AND SWIMMING INCREASE OSTEOBLAST IN EPIPHYSIS RADIAL PERIMENOPAUSE MICE BONE) - ., Muliani; Karmaya, I Nyoman Mangku; Tirtayasa, Ketut (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
The aim of this study is to measure the effect(s) of orally administered calcium lactate and swimmingactivity to the increase of osteoblasts in the epiphysis of radial bone at perimenopause stage. We usedmice of Mus musculus species age 15-16 months as experimental animals in this particular study. Forexperimental design we used Pre-test and Post-test Control Group Design. There were 4 experimentalgroups: Control; Calcium lactate administration; Swimming activity; and Combination of calcium lactateand swimming activity. Each group contained 22 mice and treatments were given to each group for sixweeks (42 days). Our results showed that following treatment, the average numbers of osteoblasts were9.46±1.81; 26.58±2.82; 25.05±2.68; 59.38±2.91 in Control, Calcium lactate administration, Swimmingactivity, and Combination of calcium-lactate administration and swimming activity groups respectively.There was a significant difference in average osteoblasts between the Control group and the other 3 groups(p<0.05) and there was no significant difference between the Calcium lactate administration and Swimmingactivity groups (p>0.05). The increase number of osteoblasts in the Combination group was larger than theother groups. In conclusion, administration of calcium lactate or swimming activity could increase thenumber of osteoblasts in mice, and the increase is larger when applied in combination.
Keywords: osteoporosis, calsium lactate, swimming, osteoblast